PRAGMATIC LEVEL ANALYSIS OF ‘AKU’ BY CHAIRIL ANWAR POETRY TRANSLATION - Annisa Nurul Firdausi; Liann Camille Davalos Perez; Teguh Setiawan (PARADIGM: Journal of Language and Literary Studies, 2023)
This study examines the poem translation of ‘Aku’ by Chairil Anwar into ‘Me’ translated by Burton Raffel. 'Aku' was written in 1943, while the translation was done years later in 1970. Poetry translation can be a challenging yet exciting field to discuss. This study investigates the pragmatic level and the strategy used in translating the poem. While translating poetry, one must understand the implied and inferred meaning of the poet. Thus, the translation must also be able to provide the same image as the original. This study employed a descriptive-qualitative study and applied the analysis of Nida and Taber’s (1974) translation strategy. The result shows that pragmatic devices such as context, speech act, and maxim can be used to understand better the context, tone, and theme of the poetry. The analyses of the strategy are also conveyed to get the inferred meaning of both the original poet and translator. The translator uses sense-for-sense translation to grasp the same image on the target text. Although the translated work’s diction, rhyme, and metaphor are not as depth as the original work, the translated work’s emotion and sense can still be felt as the original work.